DAMPAK PRESIDENTIAL THRESHOLD TERHADAP PERGANTIAN ANTAR WAKTU DI DAERAH - Harun Fadhli; Sarip Sarip; Nur Rahman (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2020)
A very difficult choice when faced with the full rights and formal requirements that have been taken, must respect the legal consequences of the single supporting party. As conceptualized by Sebastian Harnich, he will describe the relationship between theatrical stages in giving a formal impression of extra politics in Cirebon Regency. Different things happened in Cirebon Regency when the PAW took place, where regarding the single party proposing it was very clear that it did not violate the law. However, the situation becomes different when political power is mobilized to strengthen regional power. So the authors are interested in studying the impact of the regent threshold in PAW practices that are different from other regions. Then the researchers conducted a study entitled